Factors associated with early non‐response within an Internet‐based behavioural weight loss program. (9th May 2019) - Unick, J. L.; Ross, K. M.; Wing, R. R.
Summary: Objective: While behavioural weight loss interventions are effective overall, many individuals fail to achieve a clinically significant weight loss. Given that 4‐week weight loss has been shown to predict longer term outcomes, one potential strategy for improving rates of success is to provide additional support to early non‐responders. To inform these early rescue efforts, it is important to first identify how they may differ from their more successful peers. Methods: At week 4 of a 12‐week Internet‐delivered weight loss program, 130 adults (age: 49.8 ± 9.8 years, body mass index: 31.2 ± 4.6 kg m −2 ) were asked to complete an 11‐item survey assessing mood and weight‐related cognitions and behaviours. Participants were then categorized as early non‐responders (4‐week weight loss <2%) or initial responders (4‐week weight loss ≥2%), and groups were compared on intervention adherence during weeks 1–4 and week 4 survey question responses. Results: Early non‐responders and initial responders did not differ on any intervention adherence variables ( p s > 0.05). Compared to initial responders, early non‐responders reported less positive mood ( p  = 0.011), greater boredom with weight loss efforts ( p  = 0.036), greater temptation to eat foods not consistent with their goals ( p  = 0.023), and that their eating choices were less consistent with their goals ( p  < 0.001). Conclusions: These findings identify important differences between early non‐responders and initial responders, offering potential intervention targets for rescuing early non‐responders (i.e. making it easier for individuals to choose healthier foods, reducing boredom in Internet‐delivered weight loss programs and providing strategies to limit exposure to dietary temptations).